PERBAIKAN PROSES PRODUKSI TIANG LAMPU MENGGUNAKAN METODE VALUE STREAM ANALYSIS TOOLS (VALSAT) - Sari, Rahmi M.; Yuman, Syafiq Alhadi; Ishak, Aulia; Tarigan, Indah Rizkya (Smart Education, 2025)
Abstract:In the current modern era, the competitive situation of the manufacturing industry has increased and is very tight. The importance of production efficiency in a company is to increase revenue, which is the goal of every company by minimizing waste. One approach used to minimize waste is lean manufacturing. The study was conducted on a company that produces and markets products in the form of lamp posts on public roads and toll roads. The problem that often occurs in the manufacturing process of product items is that many production processes are not achieved according to the standard time set by the Company. In this study, a Lean Manufacturing analysis was carried out to improve the lamp post production process using the Value Stream Analysis Tools (Valsat) method. Based on this study, the type of waste waiting is the most dominant type of waste with a percentage of 19.55%. In second place is the type of waste overproduction with a cumulative percentage of 18.54% while waste motion is 17.32%. Based on the current state value stream mapping, the process cycle efficiency of the Hexagonal Lamp Post manufacturing process is 98%. Keyword:Lean Manufacturing, Waste, Value Stream Analysis Tools, Process Cycle Efficiency Abstrak:Pada era modern saatinisituasipersainganindustri manufakturmengalamikenaikan dan sangat ketat.Pentingnyaefisiensiproduksidalamsebuahperusahaanadalahuntukmeningkatkanpendapatandimanahalinimerupakantujuansetiap perusahaandenganmemperkecilterjadinyawaste. Salah satupendekatan yang digunakanuntukmeminimalisirwasteadalahlean manufactring.Penilitiandilakukan pada perusahaan yang memproduksisertamemasarkanprodukberupatiang-tianglampu yang ada di jalanruasjalanumum dan jalantol. Permasalahan yang seringterjadi pada proses manufaktur item produkmasihbanyak proses produksi yang tidaktercapaidengansesuaiwaktustandar yang sudahditetapkan oleh Perusahaan. Dalam penelitianini, dilakukananalisisLeanManufacturinguntukperbaikan proses produksitianglampumenggunakanmetodeValueStreamAnalysisTools (Valsat). Berdasarkanpenelitiantersebutdiperolehjeniswaste waitingmerupakanjeniswaste yang paling mendominasidenganpersentasesebesar 19,55%. Pada urutankeduaterdapatjeniswaste overproductiondenganpersentasekumulatifsebesar 18,54% sedangkanwaste motionsebesar 17,32 %. Berdasarkancurrent state value stream mapping, process cycle eficiency proses pembuatanTiangLampu Hexagonal diperolehnilai 98 %. Kata kunci:Lean Manufacturing, Waste, Value Stream Analysis Tools, Process Cycle Efficiency